Global burden of metabolic dysfunction-associated steatotic liver disease, 2010 to 2021 - Gong Feng; Giovanni Targher; Christopher D. Byrne; Yusuf Yilmaz; Vincent Wai-Sun Wong; Cosmas Rinaldi Adithya Lesmana; Leon A. Adams; Jerome Boursier; George Papatheodoridis; Mohamed El-Kassas; Nahum Méndez-Sánchez; Silvia Sookoian; et al. (JHEP Reports)
Background & Aims: This study used the Global Burden of Disease data (2010–2021) to analyze the rates and trends of point prevalence, annual incidence, and years lived with disability (YLDs) for metabolic dysfunction-associated steatotic liver disease (MASLD) in 204 countries. Methods: Total numbers and age-standardized rates per 100,000 population for MASLD prevalence, annual incidence, and YLDs were compared across regions and countries by age, sex, and sociodemographic index (SDI). Smoothing spline models were used to evaluate the relationship between the burden of MASLD and SDI. Estimates were reported with uncertainty intervals (UI). Results: Globally, in 2021, the age-standardized rates per 100,000 population of point prevalence of MASLD were 15,018.1 cases (95% UI 13,756.5–16,361.4), annual incidence rates were 608.5 cases (598.8–617.7), and YLDs were 0.5 (0.3–0.8) years. MASLD point prevalence was higher in men than women (15,731.4 vs. 14,310.6 cases per 100,000 population). Prevalence peaked at ages 45–49 for men and 50–54 for women. Kuwait (32,312.2 cases per 100,000 people; 95% UI: 29,947.1–34,839.0), Egypt (31,668.8 cases per 100,000 people; 95% UI: 29,272.5–34,224.7), and Qatar (31,327.5 cases per 100,000 people; 95% UI: 29,078.5–33,790.9) had the highest prevalence rates in 2021. The largest increases in age-standardized point prevalence estimates from 2010 to 2021 were in China (16.9%, 95% UI 14.7%–18.9%), Sudan (13.3%, 95% UI 9.8%–16.7%) and India (13.2%, 95% UI 12.0%–14.4%). MASLD incidence varied with SDI, peaking at moderate SDI levels. Conclusions: MASLD is a global health concern, with the highest prevalence reported in Kuwait, Egypt, and Qatar. Raising awareness about risk factors and prevention is essential in every country, especially in China, Sudan and India, where disease incidence and prevalence are rapidly increasing. Impact and implications: This research provides a comprehensive analysis of the global burden of MASLD, highlighting its rising prevalence and incidence, particularly in countries with varying sociodemographic indices. The findings are significant for both clinicians and policymakers, as they offer critical insights into the regional disparities in MASLD burden, which can inform targeted prevention and intervention strategies. However, the study’s reliance on modeling and available data suggests cautious interpretation, and further research is needed to validate these findings in clinical and real-world settings.